Decision Support System for West Manggarai Tour Packages Using the SMART Method - Elisabeth Winarni (Jurnal Mandiri IT, 2020)
This Labuan Bajo Tourism Package Decision Support System is a decision support system created to assist tourists in determining the tour package that best fits the criteria based on the budget, length of trip and the weight of the destination desired by tourists. This Decision Support System uses the SMART (Simple Multi Attribute Rating Technique) method, the higher the weight of the criteria given, the greater the percentage of packages offered. This system has data on tourist attractions in Labuan Bajo which serves to support the decision-making process. The data entered in this system is in the form of the maximum package price and the desired length of the package trip. This system is built using ZK Framework scripting language with MySQL database and Apache web server.